2013
DOI: 10.3389/fphys.2013.00160
|View full text |Cite
|
Sign up to set email alerts
|

Leptin expression affects metabolic rate in zebrafish embryos (D. rerio)

Abstract: We used antisense morpholino oligonucleotide technology to knockdown leptin-(A) gene expression in developing zebrafish embryos and measured its effects on metabolic rate and cardiovascular function. Using two indicators of metabolic rate, oxygen consumption was significantly lower in leptin morphants early in development [<48 hours post-fertilization (hpf)], while acid production was significantly lower in morphants later in development (>48 hpf). Oxygen utilization rates in <48 hpf embryos and acid productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…In leptin receptor knockout medaka, largely deposits of visceral fat were observed 49. In leptin -A knockdown zebrafish embryos, the metabolic rate and oxygen consumption are significantly lower than in un-treated embryos 50. In leptin receptor knockout zebrafish, it has been shown that leptin is not required for adipostasis, food intake, or reproduction, but retains a role in the regulation of glucose homeostasis 51.…”
Section: Discussionmentioning
confidence: 99%
“…In leptin receptor knockout medaka, largely deposits of visceral fat were observed 49. In leptin -A knockdown zebrafish embryos, the metabolic rate and oxygen consumption are significantly lower than in un-treated embryos 50. In leptin receptor knockout zebrafish, it has been shown that leptin is not required for adipostasis, food intake, or reproduction, but retains a role in the regulation of glucose homeostasis 51.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in zebrafish, knocking down lepA decreases metabolic rate (Dalman et al, 2013) and in golden pompano, Trachinotus blochii (Perciforme), lepA gene polymorphisms are associated with different body weights, heights and lengths (Wu et al, 2016). Whereas in mammals, leptin acts as an adipostat and its plasma levels are proportional to the amount of body fat, there is little evidence for such a role in fish.…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…Although the tissue distribution pattern of A and B are discrete (suggesting functional differences, (Angotzi et al, 2013; Gorissen et al, 2009), a great majority of fish studies exclusively focus on leptin A (Dalman et al, 2013; Frøiland et al, 2010; Huising et al, 2006; Liu et al, 2012). To date, functional study of leptin B has been limited to expression studies (responds to food restriction- Gorissen et al, 2009; increases during early development- Angotzi et al, 2013), and all manipulations using species-specific recombinant leptins have used leptin A (Dalman et al, 2013; Liu et al, 2012; Lu et al, 2012; Murashita et al, 2011, 2008). …”
Section: Basal Vertebrates Express Multiple Leptin Orthologsmentioning
confidence: 99%
“…Dalman et al, 2013; Mariano et al, 2013 in fishes; Lõhmus et al, 2004 in birds; French et al, 2011 in lizards; Crespi et al, 2012; Hicks-Courant, M.L. and Crespi, E.J., 2006 in amphibians), but recent studies emphasize the role leptin plays in energetic tradeoffs between the immune system and other physiological systems (see Demas, 2004).…”
Section: Leptin As An Immunomodulatormentioning
confidence: 99%